Usability of SAP ERP HCM and Workarounds: A Case Study on Payroll Productivity and Organizational Efficiency from an Employee Perspective - Urpanen, Lotta (My University, 2024)
Enterprise systems like SAP Payroll play a crucial role in streamlining organizational processes, yet their usability significantly impacts efficiency and user satisfaction. This study examines SAP Payroll's usability within Company X, focusing on how it influences payroll professionals' daily workflows and organizational productivity. By identifying key challenges, workarounds, and improvement opportunities in system usage, this research aims to enhance the understanding of how complex systems can be optimized to support expert work and improve organizational outcomes. This research investigates the usability of the SAP Payroll system at Company X and its impact on organizational efficiency. The research focuses on understanding the factors that hinder the smooth use of the system and how these professionals adapt to overcome these limitations. Through qualitative interviews with payroll specialists, the study identifies common obstacles related to system complexity, user interface design, and data processing. The findings highlight the role of neutral workarounds, particularly the extensive use of Excel, in enhancing work efficiency. Despite the benefits of the SAP Payroll system, such as streamlined payroll processing and reporting capabilities, the complexity of the system and lack of adequate training and support lead to challenges and inefficiencies. The research aims to identify the most common challenges faced by payroll professionals in using the system and explores potential solutions to address these issues, such as improved training and support mechanisms. The study also underscores the importance of a structured onboarding process and continuous feedback loops in maintaining system usability and employee engagement. The research identified several recurring challenges with SAP Payroll, including limited knowledge of mass tools, cumbersome reporting processes, and insufficient support for specific local requirements, such as tax automation. Many users have devised workarounds, such as utilizing Excel for advanced data analysis and automation tasks. These adaptations, while efficient in the short term, underscore gaps in system training and functionality. Additionally, user experience varied significantly based on individual technical expertise and familiarity with SAP's logic, highlighting the need for role-based training. The findings suggest that addressing usability challenges in SAP Payroll requires a dual focus: improving technical training and enhancing system features. Organizations can benefit from structured onboarding programs tailored to various user roles, emphasizing practical scenarios and regular feedback. From a research perspective, this study contributes to the broader discourse on enterprise system adoption, suggesting avenues for future exploration into the long-term impacts of workarounds on data integrity and organizational performance. Additionally, the importance of fostering collaborative learning environments and cross departmental knowledge sharing emerged as critical factors for maximizing the potential of complex systems like SAP Payroll.
Keywords: SAP ERP HCM, SAP Payroll, usability, usability challenges, payroll professionals, workarounds, Excel, system complexity, employee training, organizational support